2021
DOI: 10.3390/ijms22189888
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Fusarium Mycotoxins and Lytic Enzymes during Pea Plants’ Infection

Abstract: Fusarium species are common plant pathogens that cause several important diseases. They produce a wide range of secondary metabolites, among which mycotoxins and extracellular cell wall-degrading enzymes (CWDEs) contribute to weakening and invading the host plant successfully. Two species of Fusarium isolated from peas were monitored for their expression profile of three cell wall-degrading enzyme coding genes upon culturing with extracts from resistant (Sokolik) and susceptible (Santana) pea cultivars. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Compounds such as lignin and resin generated in the woody tissue have the ability to create a protective barrier surrounding the polysaccharides and protein molecules of plant tissues. This barrier serves to hinder fungi from infiltrating through the hydrolysis of plant tissues, thereby bolstering the plant's resistance to diseases [54][55][56]. The study's findings revealed an increase in the type and content of secondary metabolites when comparing the induction of burning holes with the induction of drilling combined with fungi.…”
Section: Discussionmentioning
confidence: 92%
“…Compounds such as lignin and resin generated in the woody tissue have the ability to create a protective barrier surrounding the polysaccharides and protein molecules of plant tissues. This barrier serves to hinder fungi from infiltrating through the hydrolysis of plant tissues, thereby bolstering the plant's resistance to diseases [54][55][56]. The study's findings revealed an increase in the type and content of secondary metabolites when comparing the induction of burning holes with the induction of drilling combined with fungi.…”
Section: Discussionmentioning
confidence: 92%
“…The isolate HF4 recorded the highest infection percentage, reaching 93.3%, while the infection percentage for the other isolates ranged between 70 -76.0%. The reason for the ability of the pathogenic fungus to cause infection may be due to its ability to attack seeds, causing them to rot and decompose as a result of its secretion of cellulose and pectin-degrading enzymes in the early stages of infection, which plays a role in the process of penetrating the host [20]. Due to the high efficiency of the isolate HF4 in laboratory and field infection, which was obtained from Wasit-Sheik Saad, it was selected for the subsequent experiments.…”
Section: Testing the Pathogenicity Of Fusarium Spp Fungal Isolates In...mentioning
confidence: 99%
“…As a result, recent techniques for accurately identifying Fusarium species combine morphological traits with multi-gene molecular phylogenetic analyses (Jedidi et al, 2021). Fusarium species generate a variety of secondary metabolites, including mycotoxins and extracellular cell wall-degrading enzymes (CWDEs), which aid in weakening and successfully invading the host plant (Perincherry et al, 2021). The present study aimed to investigate the disease prevalence of Fusarium wilt pathogens that attach cucumber grown in greenhouses in different regions of Babylon Province, and to identify the causal agents using morphological characteristics and sequencing of Internal transcribed spacer (ITS) region and pathogenicity of the causative agents of Fusarium wilt disease.…”
Section: Introductionmentioning
confidence: 99%